Ewing’s sarcoma or peripheral primitive neuroectodermal tumor at the base of tongue: a rare location case report - Devi, Pinki; Anjali; Yadav, Nidhi; Singh, Sunita; K. S. Tomer, Manoj (International Journal of Research in Medical Sciences, 2023)
Peripheral primitive neuroectodermal tumor now termed as Ewings sarcoma/PNET, representing a family of tumors with varying degrees of neuronal differentiation and genetic rearrangements. Most common sites are extraosseous involving trunk and lower limb. Base of tongue is a very rare site for Ewing’s/PNET, hence in view of rarity of the location as an uncommon presentation, the case has been reported for the better understanding and supporting the literature with the similar finding. A 68 years old female patient presented with the complaint of difficulty in swallowing since 3 months. On examination growth was identified at the left side base of tongue. Biopsy was processed and stained with H&E and other relevant markers. Differentials on the basis microscopic examination were lymphoma, neuroendocrine tumor and primitive neuroectodermal tumor. Various immunohistochemical markers to rule out the given differential were used. The tumor was positive for CD 99 and vimentin. The case was repored as PNET. Peripheral PNET is a challenging topic. Wide range of extraosseous locations have been observed but head and neck being less reported needs to be studied for understanding the behavior of this highly malignant disease in this rare location so that patient can be benefitted by advanced multimodality treatments including surgery, chemotherapy and radiotherapy.